“Enfranchised” Language in Mulcaster’s Elementarie and Shakespeare’s Henry V - Leonard, Alice (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
This article is a study of early literary theory and practice in Renaissance England, which focuses specifically on Shakespeare’s language use. The end of the sixteenth century in England experienced a linguistic revolution as Latin was gradually replaced by vernacular English. Renaissance rhetoricians such as George Puttenham and Thomas Wilson patriotically argued that English was capable of employing figures of speech to express complex ideas. Yet in this period the vernacular was in a process of formation, demonstrated by Richard Mulcaster’s Elementarie (1582). He argued for the expansion of the lexicon according to “enfranchisement”: the welcoming and naturalizing of foreign words from Latin, Greek, Spanish, French and Italian into English (1582: 172). The Elementarie reveals how language was being shaped in a period of massive linguistic change. This is especially visible in the dynamic creativity of Shakespeare’s linguistically-inventive drama, made possible by the transition from Latin to a protean vernacular. He staged the difference within English itself and its mixing with foreign languages. This is particularly prevalent in Henry V (1599) with the representation of French and regional dialects, where linguistic exchange and semantic negotiation bring linguistic difference to the fore and the lexical parts become all the more plastic. This article seeks to examine what happens when English is set alongside foreign tongues: why they are used, how they are represented, and how they interact. It will argue that this attention to foreign language demonstrates English inviting rather than excluding strange tongues for the health of the linguistic body and the enhancement of expression.